Empowering Marginalized Indigenous Muslim Communities Through Islamic Education - S, Sukman; Hermanto, Hermanto; Reevany Bustami, Mohammad (Jurnal Pendidikan Islam, 2025)
Educational marginalization remains a pressing issue affecting indigenous Muslim communities in Indonesia, particularly in remote and socioeconomically disadvantaged areas. This study investigates the contributions and challenges of the Emeyodere Islamic Educational Institution in supporting the Kokoda Victory Muslim community in Sorong City, West Papua. Using a qualitative research design, the study draws on field observations and in-depth interviews to examine how the institution fosters educational inclusion among the marginalized Kokoda Tribe. Findings reveal that the institution plays a pivotal role in transforming educational outcomes through a core ethos grounded in mutual encouragement, care, respect, and motivation. Emeyodere has significantly expanded access to education for Kokoda children, enabling some to pursue higher education and secure professional careers, including civil service. The institution also serves as a cultural and religious hub, reinforcing Islamic identity in the midst of social exclusion. Despite its success, the institution grapples with numerous challenges, such as limited parental awareness of Islamic education, inadequate infrastructure, and a shortage of trained educators. The study implies that community-based Islamic education, when rooted in strong local leadership and social capital, can serve as a powerful tool for empowering marginalized groups and advancing educational equity in Indonesia’s eastern peripheries.